THE IMPACT AND PUBLIC’S PERCEPTIONS ON THE TURNING OF TAJWID LAKE INTO A TOURIST ATTRACTION - Anggi Arrahman; Achmad Hidir (Bajang Institute, 2021)
This research was aimed to determine the public’s perceptions toward the attraction of Tajwid Lake. This research was also to describe the impact of Tajwid Lake attraction on local communities.The methodology used in this research was qualitative method. The data source in this research was consisted of primary and secondary data. Data collecting technique used in this research were participatory observation, in-depth interview, documentation and literature review. This research was conducted for two months. The results of the study indicated that the turning of Tajwid Lake into a tourist spot cannot be separated from various problems that cause the various public’s perceptions, both pros and cons. The impact of turning Tajwid Lake into a tourist spot is the presence of a recreation area for the community and providing space to increase income such as selling and providing services for tourists so that it can help the community's economy. However, it also has a negative impact on the community, especially those who make a living as fishermen, it because Tajwid Lake was place for fishermen to get their fish. Since Tajwid Lake became a tourist spot, it has been difficult to get the fish due to the dredging of the lake for tourism purposes, as well as restrictions for fishermen looking for fish in the lake to avoid the interfere with tourist activities. It caused the fishermen losing their place to get fish. Therefore at the time they looked for fish to go far up the river, and reduced the catches which have an impact on their economy.